A Bird’s Eye View on the Origin of Aortic Hemogenic Endothelial Cells - Seco, Pedro; Martins, Gabriel G.; Jacinto, António; Tavares, Ana Teresa (Frontiers in Cell and Developmental Biology, 2020)
During early embryogenesis, the hemogenic endothelium of the developing dorsal aorta is the main source of definitive hematopoietic stem cells (HSCs), which will generate all blood cell lineages of the adult organism. The hemogenic endothelial cells (HECs) of the dorsal aorta are known to arise from the splanchnic lateral plate mesoderm. However, the specific cell lineages and developmental paths that give rise to aortic HECs are still unclear. Over the past half a century, the scientific debate on the origin of aortic HECs and HSCs has largely focused on two potential and apparently alternative birthplaces, the extraembryonic yolk sac blood islands and the intraembryonic splanchnic mesoderm. However, as we argue, both yolk sac blood islands and aortic HECs may have a common hemangioblastic origin. Further insight into aortic HEC development is being gained from fate-mapping studies that address the identity of progenitor cell lineages, rather than their physical location within the developing embryo. In this perspective article, we discuss the current knowledge on the origin of aortic HECs with a particular focus on the evidence provided by studies in the avian embryo, a model that pioneered the field of developmental hematopoiesis.